Carbonic anhydrase inhibition and cytotoxicity studies of Mannich base derivatives of thymol. (1st November 2016) - Inci Gul, Halise; Yamali, Cem; Tugce Yasa, Asiye; Unluer, Elif; Sakagami, Hiroshi; Tanc, Muhammet; Supuran, Claudiu T.
Abstract: Mannich bases of thymol were synthesized. The aminomethylation reaction was realised in the ortho position of the phenol for compounds2 (dipropylamine), 3 (benzylamine), and4 (dibenzylamine) while it was from para position for1 (dimethylamine), 5 (piperidine), 6 (morpholine) and7 ( N -methylpiperazine). The carbonic anhydrase (CA, EC 4.2.1.1) inhibitory effects of the compounds were asssessed against hCA I and hCA II. All compounds moderately inhibited hCA I and hCA II. The cytotoxicity of the compounds against four human oral squamous cell carcinoma cell lines were compared those against three normal oral cells. Tumor specificity values were about 2 or slightly more for the compounds2, 3, 4, 5 and6 . Compound2 showed cytostatic activity against OSCC cell lines at 16 to 32-fold lower concentrations as compared with normal cells. This suggests that compound2 can be considered as cytotoxicity enhancing drug candidate for further investigations.